TINGKAT PENGETAHUAN AKUNTAN MUDA DALAM MENJAGA EKSISTENSI AKUNTANSI SYARIAH GUNA MENYONGSONG INDONESIA EMAS 2045 - Artichah, Gusti B'tari; Nawang Wulan, Gracia Angelina (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Accounting has undergone many developments in line with efforts to adapt to the needs of stakeholders. This development can be seen from the introduction of sharia-based accounting principles with the emergence of many sharia transactions offered by sharia entities. This is the background for the birth of SAK Syariah which was ratified in 2007. With the development of studies on Islamic accounting in Indonesia, accountants are required to equip themselves with good knowledge of Islamic accounting. Therefore, this study aims to determine the Islamic accounting knowledge of young accountants in order to welcome Indonesia Golden era 2045 in terms of their knowledge of Islamic accounting. This research is a descriptive study using a quantitative approach with a survey method. The results found that the knowledge of sharia accounting possessed by young accountants was still considered less ready to contribute to realizing Indonesia Golden era 2045. It was also found that the factors that led to the lack of knowledge of sharia accounting experienced by young accountants namely: lack of literature, lack of practice-based learning, lack of educators who are experts in their fields, religious stereotypes, assumptions are the same as conventional accounting. Furthermore, this study suggests optimizing young accountants' understanding of Islamic accounting in addition to conventional accounting. This is beneficial for efforts to develop Islamic accounting in Indonesia and for Islamic institutions to be able to present financial reports correctly and adequately.